Symbiotic seed germination of an endangered epiphytic slipper orchid, Paphiopedilum villosum (Lindl.) Stein. from Thailand - Khamchatra, N.; Dixon, Kingsley; Tantiwiwat, S.; Piapukiew, J. (Elsevier BV, 2016)
Published by Elsevier B.V. Paphiopedilum villosum (Lindl.) Stein is a native epiphytic slipper orchid in Thailand. This species is now being threatened and endangered. Propagation of this species is essential for conservation and reintroduction purposes. In this study, the propagation of P. villosum was achieved through the in vitro asymbiotic and symbiotic seed germination. Seeds of P. villosum sown on asymbiotic media, Murashige and Skoog (MS), Vacin and Went (VW) and Thomale GD (TH), did not germinate within 16. weeks. Seven different fungal strains were isolated from roots of this orchid species. The germination rate index (GRI) and the development rate index (DRI) of P. villosum seeds in treatments inoculated with fungal isolates PVCP01, PVCP05, and PVCP06 was significantly higher than uninoculated control treatments. Fungal isolate PVCP01 significantly increased the GRI and DRI of every stage of protocorm development, whereas fungal isolates PVCP05 and PVCP06 were only able to promote seed germination and protocorm development to stage 2. As for the wild orchid species, P. villosum, a compatible fungus is therefore required for promoting seed germination and protocorm development. Based on analysis of morphological characters and sequences of the nuclear ribosomal transcribed spacer (ITS), fungal isolates PVCP01, PVCP 05, and PVCP06 were identified as Tulasnella sp., Ceratobasidium sp., and Flavodon sp., respectively. The information obtained from this study will be used to propagate other threatened Thai orchids for conservation and reintroduction programs.